Overview for the study of P2 receptors: From P2 receptor history to neuropathic pain studies - Kazuhide Inoue (Elsevier, 2022)
Since new roles of nucleotides as neurotransmitters were proposed by Geoffrey Burnstock, the roles of ATP and P2 receptors (P2Rs) have been extensively studied in pain signaling. This review primarily focuses on the history and roles of P2X2Rs and P2X2/3Rs in acute and chronic pain, and P2X4Rs in neuropathic pain after peripheral nerve injury (PNI). Spinal microglial activity mediated by P2X4Rs shows a very important contribution to evoking neuropathic pain, and P2X4Rs might be targets for the treatment of neuropathic pain. The advantage of P2X4Rs of microglia as therapeutic targets is that P2X4Rs are predominantly enhanced in activated microglia after PNI, and P2X4R blockers do not affect normal pain signaling. Currently, many excellent P2R-related drug candidates are being developed, and it seems that the day when we will use them in clinical practice is not too far away.